1999
DOI: 10.1007/s11664-999-0220-x
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen incorporation in AllnP, and its effect on P-type doping with magnesium

Abstract: Oxygen incorporation in Al y In 1-y P (y ~ 0.5) grown by metalorganic chemical vapor deposition (MOCVD) has been studied as a function of PH 3 flow, growth temperature, and alloy composition. Both O 2 and diethylaluminum ethoxide (DEAlO) were employed as sources of oxygen. The incorporation of oxygen was found to be a superlinear function of O 2 or DEAlO flow. When multiple sources of oxygen are present, a surface interaction leads to enhanced oxygen incorporation. Oxygen incorporation cannot be adequately des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 36 publications
1
12
1
Order By: Relevance
“…Thus, any growth parameters or impurity species that alter donor or acceptor incorporation or diffusion properties may have important implications on device design, and it is, therefore, important to thoroughly understand such effects. With regard to such properties, we have previously demonstrated that the deep donor, oxygen, enhances Mg incorporation in Al 0.5 In 0.5 P. 3 Similar to our previous observations regarding Mg-oxygen interactions in Al 0.5 In 0.5 P, various other research groups have reported that shallow-donor species, such as S or Si, have enhanced acceptor incorporation in III-V semiconductors. [4][5][6][7][8][9][10][11][12][13] In addition to enhancing acceptor incorporation, such shallow-donor species have also been shown to suppress acceptor diffusion in III-V semiconductors, [4][5][6][7][8][9][10][11][12][13] thus providing motivation to investigate the potential impact of the deep donor, oxygen, on Mg diffusion in Al 0.5 In 0.5 P. In addition to this investigation of Mg-oxygen dopant interactions in Al 0.5 In 0.5 P, we also consider donor-acceptor interactions between Mg and the shallow donors, Te, S, and Si, to allow the reader to more effectively compare our results on Mg-oxygen dopant interactions to previous reports on dopant interactions between shallow donors and Zn or Mg acceptors.…”
Section: Introductionsupporting
confidence: 87%
See 3 more Smart Citations
“…Thus, any growth parameters or impurity species that alter donor or acceptor incorporation or diffusion properties may have important implications on device design, and it is, therefore, important to thoroughly understand such effects. With regard to such properties, we have previously demonstrated that the deep donor, oxygen, enhances Mg incorporation in Al 0.5 In 0.5 P. 3 Similar to our previous observations regarding Mg-oxygen interactions in Al 0.5 In 0.5 P, various other research groups have reported that shallow-donor species, such as S or Si, have enhanced acceptor incorporation in III-V semiconductors. [4][5][6][7][8][9][10][11][12][13] In addition to enhancing acceptor incorporation, such shallow-donor species have also been shown to suppress acceptor diffusion in III-V semiconductors, [4][5][6][7][8][9][10][11][12][13] thus providing motivation to investigate the potential impact of the deep donor, oxygen, on Mg diffusion in Al 0.5 In 0.5 P. In addition to this investigation of Mg-oxygen dopant interactions in Al 0.5 In 0.5 P, we also consider donor-acceptor interactions between Mg and the shallow donors, Te, S, and Si, to allow the reader to more effectively compare our results on Mg-oxygen dopant interactions to previous reports on dopant interactions between shallow donors and Zn or Mg acceptors.…”
Section: Introductionsupporting
confidence: 87%
“…The lack of such narrow Mg spikes in the oxygen-counterdoped regions A and C of Fig. 2 indicates that electrical compensation is probably not a significant factor in the effect of oxygen on Mg diffusion in Al 0.5 In 0.5 P. In fact, previous studies of oxygen electrical activity in Al 0.5 In 0.5 P suggest that only ϳ10-30% of the oxygen is electrically active, while the remaining oxygen atoms do not compensate acceptors in Al 0.5 In 0.5 P. 3,26 Yet, a third type of donor-acceptor interaction is illustrated in Fig. 6 for the Si-counterdoped sample where Si appears to have a transient-like effect on Mg incorporation at locations where the Si 2 H 6 flow was turned on or off.…”
Section: Comparison Of the Effect Of Oxygen Te S And Si On Mg Incomentioning
confidence: 67%
See 2 more Smart Citations
“…It has been reported experimentally for AlGaInP that the co-doping of Mg enhances the incorporation efficiency of O and vice versa. 20 In addition to single-photon transitions shown in Fig. 1(b), there are two-photon processes consisting of valence-band-to-IB and IB-to-conduction-band transitions, both of which are optically active.…”
mentioning
confidence: 99%